Tissue oximetry by diffusive reflective visible light spectroscopy: Comparison of algorithms and their robustness. Issue 9 (10th May 2018) - Nasseri, Nassim; Kleiser, Stefan; Wolf, Ursula; Wolf, Martin
Abstract : It is essential to measure tissue oxygen saturation (StO2 ) locally and in thin layers of tissue, for example, the bronchial mucosa, skin flaps and small bones. Visible light spectroscopy (VLS) with a shallow penetration depth is suitable method. Although several VLS algorithms have been developed and described, they have not yet been compared to each other. This hinders attempts to compare the clinical results obtained by different algorithms. To address this issue, we compared the algorithms of Harrison, Knoefel, Pittman‐Duling, Sato and our OxyVLS oximeter, which applies the algorithm from Wodick and Lübbers, in a liquid phantom with optical properties of human tissue. We generally observed considerable differences between the algorithms, which were StO2 dependent. Exceptions were OxyVLS and Sato, showing a high level of agreement with negligible StO2 dependency. In spite of the considerable deviation between the other algorithms, the difference of StO2 between them in clinically normal StO2 was <10%. We did not observe any dependency of the algorithms on hemoglobin content of the phantom or temperature. Abstract : Visible light spectroscopy is an interesting method to measure local oxygenation of tissue non‐invasively and locally. There are several algorithms developed and tested. What is missing is firstly direct comparison of these algorithms in a wide range of oxygenation and secondly testing their stability in case of the variation of temperature or hemoglobin content. These two questions will be answered in this paper.